(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Physical activity and exercise on a regular basis may help you remain healthy, active, and independent as you age. Exercise is important in avoiding health problems such as heart disease and stroke. Many studies have shown the health advantages of regular exercise. The term "exercise" refers to the regular practice of doing some kind of physical activity. Exercise is essential for maintaining excellent health and a clear mind. The regular practice of some physical labor does not imply that the body is under stress; rather, it is a stress-relieving exercise. A strong work ethic requires excellent health. This article examines the evidence supporting the health benefits of exercise across the board. Physical activity and exercise may help to decrease stress and anxiety, raise happy hormones, promote self-confidence, boost brain capacity, improve memory, and strengthen our muscles and bones. It also aids in the prevention and treatment of heart disease, obesity, blood sugar swings, cardiovascular disease, and cancer.